Facile synthesis and characterization of Zn5(OH)8Cl2•H2O nanostructure for the biomethanation process - Shivaraju, Harikaranahalli Puttaiah; Ashika, Onita Nazereth; Harini, Revanna; Yashas, Shivamurthy Ravindra; Maleki, Afshin; Shahmoradi, Behzad; Yetilmezsoy, Kaan; Kitirote, Wantala (ELSEVIER, 2021)
Zn based bioactive Zn-5(OH)(8)Cl-2 center dot H2O nanostructure was synthesized by sol-gel technique and characterized. Characterization results confirmed desired functionalities such as polycrystalline structure, simonkolleite phase, functional groups, high stability and 2-D flakes like nanostructures. Zn based nanostructure influenced the microbial CH4 production rate at dose ranges of 0.2-0.4 g that was attributed to increased microbial metabolic activities under anaerobic condition. Whereas, less production of CH4 with increased dosages of 0.6-1.2 g was observed due to inhibitory effects of Zn active agents released by nanostructure. It indicated that CH4 production rate was predominantly influenced by availability and bioactive phase of Zn required for robust anaerobic biomethanation. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Functional; Sol-gel; Zn-5(OH)(8)Cl-2 center dot H2O; Hydrothermal; Crystal structure; Biomethanation; Materials Science; Physics